AN UNDERSTANDING OF GOD’S COMMAND FOR ISRAELITES “YOU SHALL NOT LEAVE ANYTHING THAT BREATHES ALIVE” IN DEUTERONOMY 20:16: AN EXEGETICAL STUDY - Kelendonu, Michael Andrew; Gosal, Fellix (Klabat Theological Review; Vol 4 No 2 (2024): Klabat Theological ReviewDO - 10.31154/ktr.v4i2.1118.83-99, 2024)
God's love is evident in all that He does. God's only actions were to demonstrate to the Israelites the wickedness of sin and to keep them living in righteousness. Chapter 20 of the book of Deuteronomy covers laws about the sixth commandment. The infallibility of the Bible is called into question in several places, most notably in Deuteronomy 20:16, when God commands the killing of all Canaanites, including women and children. God gives the order to exterminate every person living in the Canaan region. The term "עִיר" solely refers to the cities that are part of the Canaan area, not all the places they will traverse. The phrase's common meaning also aids in understanding the village and all of its residents in addition to the city, which is a sizable area. In the end, human choice determines whether they live or not. In the context of this verse, Israel must either choose to disobey God's Word or learn to rely on God to enjoy the intrinsic, which is the Promised Land. God's love and justice are assurances of His concern for His people. Keywords: Israelites, Canaanites, Love, Justice, sixth-commandment